Specification of cross nonlinear vibration Of viscoelastic affective bar. (Latakia University Journal -Basic Sciences Series, 2018)
this paper presents a solution of non-linear viscoelastic bar systems transversal vibrations problems in presence of biological factor. Governing differential equations were built, then analytical expressions of the solution of this equations were found, which describe transversal vibrations of a thin finite length bar.